1974
DOI: 10.1258/002367774780943977
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous epizootic of pneumococcus infection in guinea-pigs

Abstract: SUMMARYType 19 Diplococcus pneumoniae was identified as the organism responsible for an outbreak of pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Streptococcus pneumoniae, particularly type 19 (Keyhani.& Naghshineh, 1974), is a well-recognized pathogen for guinea-pigs, causing septicaemia with Sebesteny exudative pleuropneumonia and pericarditis, either alone or in conjunction with other, secondary invaders. These latter may well overgrow pneumococci, especially in tissue fluids or liquid cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumoniae, particularly type 19 (Keyhani.& Naghshineh, 1974), is a well-recognized pathogen for guinea-pigs, causing septicaemia with Sebesteny exudative pleuropneumonia and pericarditis, either alone or in conjunction with other, secondary invaders. These latter may well overgrow pneumococci, especially in tissue fluids or liquid cultures.…”
Section: Discussionmentioning
confidence: 99%
“…ETIOLOGY Streptococcus pneumoniae is an oval-to lancet-shaped, encapsulated coccus that presents in pairs (diplococcus) or short chains (Fox, 2002;Percy and Barthold, 2007). S. pneumoniae is an α-hemolytic streptococcus that ferments trehalose and is optochin-sensitive (Harkness and Wagner, 1995;Keyhani and Naghshineh, 1974;Songer and Post, 2005). Additionally, it is not categorized according to one of the Lancefield groupings (Songer and Post, 2005).…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…Abortions and stillbirths can accompany a high mortality rate during an epizootic outbreak in a guinea pig colony (Percy and Barthold, 2007). CLINICAL MANIFESTATIONS In 1974, a spontaneous epizootic of respiratory infection involving 2400 guinea pigs was caused by S. pneumoniae type 19 (Keyhani and Naghshineh, 1974). During this outbreak, 450 guinea pigs died within 33 days of infection, and a short course of listlessness and failure to thrive were the only noted clinical signs prior to death.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…Although the organism is commonly found in the respiratory tracts of normal animis of these species [3, 6, 13] and healthy people [4] [5,6,13,15] but seemed to be sporadic these some decades [7,14,16].…”
mentioning
confidence: 99%
“…4 It is known that S. pneumoniae has at least 83 different serotypes, and types 19, 6, 14, 23, 3, 7 and 18 were commonly found in human being [9]. On the other hand, many investigators [5,7,13,15,16] reported epizootics of type 19 pneumococcal infection in guinea pigs. Although serotyping was not made on our pneumococcal strain, it must be important to study the possibility of transmission of the organism between human being and guinea pigs from standpoints of zoonoses.…”
mentioning
confidence: 99%